Diagnosis of iron-deficient states*. (3rd September 2015) - Archer, Natasha M.; Brugnara, Carlo
Abstract: The diagnosis of iron deficiency anemia is typically straightforward, especially when classic biochemical and hematological changes are present in a subject at risk. It can be challenging in the presence of diseases or when it is due to inherited defects of iron metabolism. The identification of iron deficiency prior to anemia development is also difficult. New hematological parameters such as reticulocyte Hb content have expanded the classic ones such as MCV, MCH and MCHC. A variety of hematology analyzers now provide novel parameters to assess cellular hypochromia and microcytosis in both reticulocytes and mature red blood cells. The repertoire of biochemical markers has also been expanded, with iron, transferrin and ferritin being supplemented by circulating transferrin receptor and hepcidin. Molecular identification of functional variants of key iron metabolism determinants has provided explanations for the heritability of some iron metabolism biomarkers. Genetic defects in some of these molecules are responsible for hereditary microcytic anemias, also called atypical microcytic anemias. In this review, we examine the most significant hematological and biochemical markers for iron metabolism, as well as relevant genetic polymorphisms and defects affecting iron handling.